2013
DOI: 10.3399/bjgp13x670697
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity after initial diagnostic excision biopsy of cutaneous melanoma in primary versus secondary care

Abstract: BackgroundCurrent UK melanoma guidelines do not support the initial diagnostic excision biopsy of pigmented lesions in primary care, although this is standard in other countries such as Australia. Previous research in Northeast Scotland found that initial diagnostic excision biopsies in primary care that prove to be melanoma were no more likely to be incomplete than those performed in secondary care, but data on longer-term outcomes were not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Finally, Peter Murchie and colleagues demonstrated that patients who had initial diagnostic excision of a pigmented lesion in primary care were no more likely to have adverse outcomes, while experiencing fewer days in hospital, than those who had their excision in hospital. 6 This tends to contradict current UK guidance to excise all pigmented lesions in secondary care.…”
mentioning
confidence: 64%
“…Finally, Peter Murchie and colleagues demonstrated that patients who had initial diagnostic excision of a pigmented lesion in primary care were no more likely to have adverse outcomes, while experiencing fewer days in hospital, than those who had their excision in hospital. 6 This tends to contradict current UK guidance to excise all pigmented lesions in secondary care.…”
mentioning
confidence: 64%
“…no evidence was found of rural patients in Northeast Scotland having higher rates of incomplete excision, nor did they have increased rates of morbidity or mortality. 6,11,12 An acknowledged limitation was that the authors only studied patients from a single health board (Grampian) in Northeast Scotland. 6,11,12 Grampian's relative affluence could potentially have masked a rural disadvantage compared with other areas, because lower socioeconomic status is associated with later diagnosis of melanoma and poorer survival.…”
Section: Introductionmentioning
confidence: 99%
“…6,11,12 An acknowledged limitation was that the authors only studied patients from a single health board (Grampian) in Northeast Scotland. 6,11,12 Grampian's relative affluence could potentially have masked a rural disadvantage compared with other areas, because lower socioeconomic status is associated with later diagnosis of melanoma and poorer survival. 13 The limitation is addressed in this study and reports the first ever investigation of the influence of rurality on the setting of melanoma excision and mortality in a whole-nation cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, for this study we were unable to differentiate between dermatologists and surgeons within the hospital group. Murchie et al [17] looked at 1263 melanoma cases in Scotland between 1991 and 2007. They examined both mortality and morbidity following initial excision in primary versus secondary care.…”
Section: Existing Literaturementioning
confidence: 99%
“…[10,14,15] Two further UK-based studies found no statistically significant difference in outcome for location of excision. [16,17] NICE performed a comprehensive review of the literature in 2009 in an attempt to identify if outcomes differ when the excisional surgery of a suspicious skin lesion is performed by a general practitioner (GP) compared with a specialist in secondary care. It concluded that the evidence for this subject was poor with only one randomized control trial existing in the literature.…”
Section: Introductionmentioning
confidence: 99%